Hubungan Asupan Vitamin C dan Vitamin E dengan Kadar LDL (Low Density Lippoprotein) pada Penderita Penyakit Jantung Koroner di Instalasi Rawat Jalan RSUD Dr. Moewardi - Rachmawati, Nisya Ayu (2016)
Coronary heart disease ( CHD ) is one of cardiovascular disease caused by constriction of the coronary blood vessels, especially caused by atherosclerosis plaque. High fat diets could increase the LDL that can lead to the atherosclerosis. Vitamin C and vitamin E are sources of antioxidant that can prevent lipid oxidation in plaques. To determine the correlation between intakes of vitamin C and vitamin E andlevel of low density lippoproteinin coronary heart disease outpatients atDr.Moewardi Hospital. This study was an observational research with cross-sectional design. The subjects were 30 patients with CHD aged 30 - 65 years. Consecutive sampling was used in this study. Data on vitamin C and vitamin E intakes were obtained through Semi Quantitative Food Frequency Quesionnare (SQFFQ) method. Data on level of LDL were obtained from medical record at Dr. Moewardi hospital. The data were analyzed used Pearson Product Moment Tests. Study showed that the average of vitamin C intake was110.803 ± 64.93 mg and 83.3% of respondents were considered to be sufficient. The average of vitamin E intake was 9.5910 ± 6.0375 mg and 100% of respondents were considered to be lack of consumption. The average of LDL level was 116.80 ± 42.266 mg/dL and 66.73% of respondents were considered to be sufficient. There was no correlation between vitamin C and vitamin Eintakesandlevel oflow density lippoproteinin coronary heart disease outpatients atDr .Moewardi Hospital (p value : 0,110 & 0,506 respectruely)